WILD ANIMALS (Uttar Pradesh, India : Om Books International, 2022)
A cute cut-out book with sweet, four-lined rhymes and colourful illustrations about adorable farm animals that make the child read and recite each page over and over again.
Keywords: Readers -- Fiction; Board books; Picture books